2011
DOI: 10.1371/journal.pone.0017988
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Human Regulatory T Cells: Analysis of CD4+CD25+FOXP3+ T Cells in Brain Lesions and Cerebrospinal Fluid of Multiple Sclerosis Patients

Abstract: Impaired suppressive capacity of CD4+CD25+FOXP3+ regulatory T cells (Treg) from peripheral blood of patients with multiple sclerosis (MS) has been reported by multiple laboratories. It is, however, currently unresolved whether Treg dysfunction in MS patients is limited to reduced control of peripheral T cell activation since most studies analyzed peripheral blood samples only. Here, we assessed early active MS lesions in brain biopsies obtained from 16 patients with MS by FOXP3 immunohistochemistry. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 45 publications
4
63
0
2
Order By: Relevance
“…Concentrations of CD4+ CD25+ FOXP3+ Treg cells are low in MS lesions; however, their numbers in peripheral blood and CSF are increased 37. This finding suggests that patients with MS do not have an insufficient number of Treg cells; rather, this regulatory cell population is dysfunctional 37.…”
Section: T-cell (Cd4+ and Cd8+) Functionmentioning
confidence: 95%
“…Concentrations of CD4+ CD25+ FOXP3+ Treg cells are low in MS lesions; however, their numbers in peripheral blood and CSF are increased 37. This finding suggests that patients with MS do not have an insufficient number of Treg cells; rather, this regulatory cell population is dysfunctional 37.…”
Section: T-cell (Cd4+ and Cd8+) Functionmentioning
confidence: 95%
“…+ T-cells that play a crucial role in maintaining self-tolerance and preventing autoimmune diseases (Sakaguchi et al 2006;Corsini et al 2011;Fritzsching et al 2011). Therefore, any therapy that leads to an increase in the number and functions of T reg cells could be considered as a potential candidate for use in the treatment of MS.…”
Section: Foxp3mentioning
confidence: 99%
“…T regulatory (Treg) cells play an opposite role to Th1 and Th17 cells. Tregs accumulate in the CNS of EAE animals, especially during the resolution phase (McGeachy et al, 2005), and impaired frequency and function of Treg cells have been reported in CNS lesions of MS patients (Fritzsching et al, 2011). The transfer of CD4 + CD25 + Treg cells protects animals from EAE (McGeachy et al, 2005), in part in an IL-10-dependent manner (Zhang et al, 2004), and Treg depletion exacerbates EAE, increasing IL-6, IL-17 and IFNc production (Reddy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%